Political participation beyond borders: a comparative analysis of Turkish youth living in home country, Germany and Belgium. (28th May 2017) - Ataman, Ayşenur; Sener, Tulin; Noack, Peter; Born, Michel
ABSTRACT: Drawing on data from a large-scale international study [PIDOP – Processes Influencing Democratic Ownership and Participation. 2009–2012. Accessed August 10.http://www.fahs.surrey.ac.uk/pidop/index.htm ], the present research examined psychological and demographic factors related to civic and political participation among adolescents and young adults (from 16 to 26 years of age) with a Turkish origin and residing in Belgium ( n  = 153), Germany ( n  = 204) and Turkey ( n  = 253). MANCOVA and one-way ANOVA were employed to address how types of civic, direct and online participation differ by socio-demographic variables. The results indicate that citizenship status was not related with the types of participation, while age, gender and country were significantly related with the type of participation in various degrees. Interaction between all the variables showed that older (20–26), foreign national, male Turkish German sample is significantly more involved in civic participation activities. Results are discussed in light of the naturalization processes of migrant groups abroad and extensive religious involvement of Turkish German sample.